Children's Rights In The Context Of Child Marriage In Gorontalo Province - Hijrah Lahaling; Siti Alfisyahrin Lasori; Kindom Makkulawuzar; Yudin Yunus; Safrin Salam (SASI, 2022)
Introduction:  The practice of child marriage is quite common and is rife in Gorontalo Province. From 2019 to 2021, there were 1,383 data on applicants for child marriage dispensation at the Religious Courts of the Gorontalo Province Regency/City.